The Arabidopsis Protein Disulfide Isomerase Subfamily M Isoform, PDI9, Localizes to the Endoplasmic Reticulum and Influences Pollen Viability and Proper Formation of the Pollen Exine During Heat Stress - Feldeverd, Elizabeth; Porter, Brad W.; Yuen, Christen Y. L.; Iwai, Kaela; Carrillo, Rina; Smith, Tyler; Barela, Cheyenne; Wong, Katherine; Wang, Pengfei; Kang, Byung-Ho; Matsumoto, Kristie; Christopher, David A. (Frontiers in Plant Science, 2020)
Plants adapt to heat via thermotolerance pathways in which the activation of protein folding chaperones is essential. In eukaryotes, protein disulfide isomerases (PDIs) facilitate the folding of nascent and misfolded proteins in the secretory pathway by catalyzing the formation and isomerization of disulfide bonds and serving as molecular chaperones. In Arabidopsis, several members of the PDI family are upregulated in response to chemical inducers of the unfolded protein response (UPR), including both members of the non-classical PDI-M subfamily, PDI9 and PDI10. Unlike classical PDIs, which have two catalytic thioredoxin (TRX) domains separated by two non-catalytic TRX-fold domains, PDI-M isoforms are orthologs of mammalian P5/PDIA6 and possess two tandem catalytic domains. Here PDI9 accumulation was found to be upregulated in pollen in response to heat stress. Histochemical staining of plants harboring the PDI9 and PDI10 promoters fused to the gusA gene indicated they were actively expressed in the anthers of flowers, specifically in the pollen and tapetum. Immunoelectron microscopy revealed that PDI9 localized to the endoplasmic reticulum in root and pollen cells. T-DNA insertional mutations in the PDI9 gene disrupted pollen viability and development in plants exposed to heat stress. In particular, the pollen grains of pdi9 mutants exhibited disruptions in the reticulated pattern of the exine and an increased adhesion of pollen grains. Pollen in the pdi10 single mutant did not display similar heat-associated defects, but pdi9 pdi10 double mutants completely lost exine reticulation. Interestingly, overexpression of PDI9 partially led to heat-associated defects in the exine. We conclude that PDI9 plays an important role in pollen thermotolerance and exine biogenesis. Its role fits the mechanistic theory of proteostasis in which an ideal balance of PDI isoforms is required in the ER for normal exine formation in plants subjected to heat stress.